Olfactory Mucosa Mesenchymal Stem Cells Ameliorate Cerebral Ischemic/Reperfusion Injury Through Modulation of UBIAD1 Expression - Liu, Jianyang; Huang, Yan; He, Jialin; Zhuo, Yi; Chen, Wei; Ge, Lite; Duan, Da; Lu, Ming; Hu, Zhiping (Frontiers in Cellular Neuroscience, 2020)
Mesenchymal stem cells (MSCs) have presented a promising neuroprotective effect in cerebral ischemia/reperfusion (I/R). Olfactory mucosa MSCs (OM-MSCs), a novel source of MSCs located in the human nasal cavity, are easy to obtain and situated for autologous transplantation. The present study was designed to evaluate the neuroprotective effects of OM-MSCs on cerebral I/R injury and the possible mechanisms. In the transient middle cerebral artery occlusion (t-MCAO) model, excessive oxidative stress and increased swollen mitochondria were observed in the peri-infarct cortex. Intravenous injection of OM-MSCs ameliorated mitochondrial damage and restored oxidant/antioxidant imbalance. Using the oxygen glucose deprivation/reperfusion (OGD/R) model in vitro, we discovered that the exposure of mouse neuroblastoma N2a cells to OGD/R triggers excessive reactive oxygen species (ROS) generation and induces mitochondrial deterioration with decreased mitochondrial membrane potential and reduces ATP content. OM-MSC transwell coculture attenuated the above perturbations accompanied with increased UbiA prenyltransferase domain-containing 1 (UBIAD1) expression, whereas these protective effects of OM-MSCs were blocked when UBIAD1 was knocked down. UBIAD1-specific small interfering RNA (siRNA) reversed the increased membrane potential and ATP content promoted by OM-MSCs. Additionally, UBIAD1-specific siRNA blocked the oxidant/antioxidant balance treated by OM-MSCs. Overall, our results suggested that OM-MSCs exert neuroprotective effects in cerebral I/R injury by attenuating mitochondrial dysfunction and enhancing antioxidation via upregulation of UBIAD1.